PENGUKURAN NILAI PANJANG KOHERENSI DUA SUMBER LASER MENGGUNAKAN INTERFEROMETER MICHELSON - Dhiesta Anggrainie; Minarni '; Tengku Emrinaldi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
One of the laser beam  unique properties is its coherence. Each  lasers  has  different coherence length. The coherence length of laser is very important in many photonic applications such as holography, spectroscopy,  and interferometry. The coherence length can be measured by an interferometer.  Measurement of coherence length of two HeNe lasers and two diode lasers has been done using a Michelson interferometer. Two HeNe lasers with same wavelength but from the different company and two diode lasers with different wavelength and  brands  were used.  The laser used were HeNe laser 632,8 nm  by Griffin  (laser I), HeNe laser 632,8 nm  by Pudak  (laser II), diode laser 638 nm(laser III) and diode laser 405 nm  (laser IV).  Interference fringes from  interferometer were  recorded  by  a  Thorlabs  CCD camera and processed using  ToupView  software  to determine the respective value of the maximum and minimum intensity  of each fringe pattern.  Data of the fringe pattern intensity were used  to calculate the visibility  (V)  and coherence length  (Lc)  of the lasers.  The results showed that Lc and deviation  of laser I was  (1,12±31,8× 10−3) mm,  laser II  was  (0,99±61,6× 10−3) mm,  laser  III  was(0,50±2,9× 10−3) mm and  laser IV was  (0,3  8±4,8× 10−3) mm, respectively .  The results also showed that the coherence lengths of the HeNe lasers were greater than the diode lasers.